2022
DOI: 10.1002/bse.3200
|View full text |Cite
|
Sign up to set email alerts
|

Pursuing a strategy of ‘common benefit’ in business: The adoption of the benefit corporation model in Italy

Abstract: A benefit corporation (BC) is a for-profit company that pursues common benefits for stakeholders. Adopting institutional theory, we analyse the characteristics of the company in relation to the common benefits a BC pursue and how BC model fits with corporate social responsibility (CSR) practices defined in literature. BCs were introduced by a 2016 law in Italy, that was the first European country to approve legislation for BCs, under which a company must indicate its specific common benefit in its articles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 63 publications
(79 reference statements)
1
5
0
Order By: Relevance
“…This study contributes to highlighting the role of stakeholders in BCs (Blasi & Sedita, 2021) and provides an in-depth case study in the BC field in response to Del Baldo's (2019) call. Moreover, we show the efforts of an enterprise transforming into a BC to integrate its interests with those of stakeholders (Marchini et al, 2022). As stated by Brown and Forster (2013) and Sen and Cowley (2013) confirming that this theoretical framework is a useful lens in the field of CSR for untangling the interactions among interests, expectations, and influence of stakeholders in organisational change (Dmytriyev et al, 2021).…”
Section: Concluding Reflectionssupporting
confidence: 71%
See 1 more Smart Citation
“…This study contributes to highlighting the role of stakeholders in BCs (Blasi & Sedita, 2021) and provides an in-depth case study in the BC field in response to Del Baldo's (2019) call. Moreover, we show the efforts of an enterprise transforming into a BC to integrate its interests with those of stakeholders (Marchini et al, 2022). As stated by Brown and Forster (2013) and Sen and Cowley (2013) confirming that this theoretical framework is a useful lens in the field of CSR for untangling the interactions among interests, expectations, and influence of stakeholders in organisational change (Dmytriyev et al, 2021).…”
Section: Concluding Reflectionssupporting
confidence: 71%
“…In particular, the authors argued how the BC label makes it possible to obtain an advantage in terms of recognition by stakeholders as an enterprise belonging to the BC community, which therefore shares the same values and principles. Recently, Marchini et al (2022) used a mixed-method approach to explore the relationship among BC transformation, strategy changes and impact areas pursued by BCs. The study showed that to have a positive impact on the community, the environment and workers, it is necessary to have constant dialogue with all stakeholders concerned.…”
Section: Benefit Corporations and Stakeholder Relationshipsmentioning
confidence: 99%
“…Dynamic capability is a company's ability to integrate, build, and reconfigure internal and external competencies to face a rapidly changing environment. Thus, dynamic capabilities reflect an organization's ability to achieve new and innovative forms of competitive advantage [43].…”
Section: Literature Reviewmentioning
confidence: 99%
“…If a collective achieves the right common goals, it can also achieve common benefits (Ekwoaba et al, 2019). Profit corporations (BC) have reached the maturity that their goal is not only individual profit but also to create common benefit for all stakeholders so that they can maintain consensus and cohesion in the company (Marchini et al, 2023).…”
Section: Theoretical Frameworkmentioning
confidence: 99%